Cardiovascular health and cognitive functioning among centenarians: a comparison between the Tokyo and Georgia centenarian studies. (21st February 2019) - Martin, Peter; Gondo, Yasuyuki; Arai, Yasumichi; Ishioka, Yoshiko; Johnson, Mary Ann; Miller, L. Stephen; Woodard, John L.; Poon, Leonard W.; Hirose, Nobuyoshi
ABSTRACT: Objectives: Centenarians have survived into very late life, but whether they reach very old age in good health remains unclear. The purpose of this study was to compare the cardiovascular health status and cognitive functioning of centenarians in the United States with centenarians in Japan. Design, Setting, and Participants: This cross-national design compared centenarians from the United States and Japan. The sample of U.S. centenarians was recruited from the Georgia Centenarian Study and included 287 centenarians. The sample of Japanese centenarians was recruited from the Tokyo Centenarian Study and included 304 centenarians. Measurements: Cognitive functioning was assessed with a mental status questionnaire, and cardiovascular disease by a health history assessment, blood pressure, and selected blood parameters. Results: The results suggest that Tokyo centenarians had lower disease experiences and BMI values, when compared to Georgia centenarians, but blood pressure was higher among Japanese centenarians. Lower levels of hemoglobin in Japanese centenarians and higher levels of C-reactive protein in Georgia were also found. The positive association of hypertension and albumin levels with cognitive functioning and the negative association of stroke occurrence with cognitive functioning were replicated in both countries. Differential effects were obtained for heart problems, BMI, and C-reactive protein (with positive effects for Tokyo centenarians, except for C-reactive protein). Conclusion: For extremely old individuals, some markers of cardiovascular disease are replicable across countries, whereas differential effects for cardiovascular health also need to be considered in cardiovascular health.